Chemotherapy-induced early transient increase and surge of CA 19–9 level in patients with pancreatic Adenocarcinoma✰. (2021) - Le, Viet H.; Franko, Jan; Paz, Benjamin I.; Singh, Gagandeep; Fakih, Marwan; Chung, Vincent
Highlights: Initial early rise of CA 19–9 levels occur in patients with advanced pancreatic adenocarcinoma during chemotherapy. CA 19–9 surge during chemotherapy for PDAC may indicate treatment response. FOLFIRINOX and nab- P + gem associate with early rise and surge of CA 19–9. In the setting of clinical stability, early transient CA 19–9 rise may not indicate progression, but rather impending response to therapy. Abstract: This study aimed to characterize chemotherapy-induced transient increase and surge of CA 19–9 level to treatment response in patients with advanced pancreatic ductal adenocarcinoma (PDAC). A retrospective case series was performed of advanced PDAC patients treated with first-line chemotherapy at City of Hope Comprehensive Cancer Center from Jan 2017 to May 2020. CA 19–9 surge was defined as an increase of >20% from baseline followed by a >20% drop in one or more subsequent CA 19–9 levels compared to baseline. Out of 106 advanced PDAC patients, 38 were evaluable for CA 19–9 surge. Fourteen (51.9%) patients treated with FOLFIRINOX and 3 (27.3%) patients treated with nab- P + Gem chemotherapy demonstrated an early transient rise in CA 19–9 level. A CA 19–9 surge was documented in 9 (23.7%) patients, all with duration of surge lasting < 16 weeks. Five out of 9 (55.6%) patients (4: FOLFIRINOX, 1: nab- P + Gem) with CA 19–9 surge demonstrated partial objective response rate on surveillance cross-sectional imaging. One patient (FOLFIRINOX) had stable disease, and 2 patients (1: FOLFIRINOX, 1: nab- P + Gem) were found to have disease progression after treatment interruption. The initial early rise of CA 19–9 levels during chemotherapy in patients with advanced PDAC may not indicate tumor progression. Rather, it may represent a chemotherapy-induced transient increase or surge phenomenon of the tumor marker in patients responding to treatment.